POWER CHARACTERISTICS OF TWO CORE MODIFIED PHASE SHIFT TRANSFORMER - Calinin L.; Zaitev D.V.; Tirshu M.; Berzan V.P.. (Problems of the Regional Energetics)
The paper is aimed to Simulink modeling of different functioning modes of two core modified phase shift transformer. This one allowing to determine power characteristics of installation, analyze and compare of results obtained by mathematical modeling and experimental data obtained by help of physical sample of installation, performed on base technical solution called “Marcereu Connection”.